LINE-1 methylation in leukocyte DNA, interaction with phosphatidylethanolamine N-methyltransferase variants and bladder cancer risk - Tajuddin, S M; Amaral, A F S; Fernández, A F; Chanock, S; Silverman, D T; Tardón, A; Carrato, A; García-Closas, M; Jackson, B P; Toraño, E G; Márquez, M; Urdinguio, R G; et al. (British journal of cancer, 2014)
Background: Aberrant global DNA methylation is shown to increase cancer risk. LINE-1 has been proven a measure of global DNA methylation. The objectives of this study were to assess the association between LINE-1 methylation level and bladder cancer risk and to evaluate effect modification by environmental and genetic factors. Methods: Bisulphite-treated leukocyte DNA from 952 cases and 892 hospital controls was used to measure LINE-1 methylation level at four CpG sites by pyrosequencing. Logistic regression model was fitted to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs). Interactions between LINE-1 methylation levels and environmental and genetic factors were assessed. Results: The risk of bladder cancer followed a nonlinear association with LINE-1 methylation. Compared with subjects in the middle tertile, the adjusted OR for subjects in the lower and the higher tertiles were 1.26 (95% CI 0.99–1.60, P =0.06) and 1.33 (95% CI 1.05–1.69, P =0.02), respectively. This association significantly increased among individuals homozygous for the major allele of five single-nucleotide polymorphisms located in the phosphatidylethanolamine N -methyltransferase gene (corrected P -interaction<0.05). Conclusions: The findings from this large-scale study suggest that both low and high levels of global DNA methylation are associated with the risk of bladder cancer.